3D Hierarchical Porous α‐Fe2O3 Nanosheets for High‐Performance Lithium‐Ion Batteries. Issue 4 (7th November 2014) - Cao, Kangzhe; Jiao, Lifang; Liu, Huiqiao; Liu, Yongchang; Wang, Yijing; Guo, Zaiping; Yuan, Huatang
<x xml:space="preserve">Abstract</x> To develop a long cycle life and good rate capability electrode, 3D hierarchical porous α‐Fe2O3 nanosheets are fabricated on copper foil and directly used as binder‐free anode for lithium‐ion batteries. This electrode exhibits a high reversible capacity and excellent rate capability. A reversible capacity up to 877.7 mAh g−1 is maintained at 2 C (2.01 A g−1) after 1000 cycles, and even when the current is increased to 20 C (20.1 A g−1), a capacity of 433 mA h g−1 is retained. The unique porous 3D hierarchical nanostructure improves electronic–ionic transport, mitigates the internal mechanical stress induced by the volume variations of the electrode upon cycling, and forms a 3D conductive network during cycling. No addition of any electrochemically inactive conductive agents or polymer binders is required. Therefore, binder‐free electrodes further avoid the uneven distribution of conductive carbon on the current collector due to physical mixing and the addition of an insulator (binder), which has benefits leading to outstanding electrochemical performance.